Characteristics of aggressive incidents in emergency primary health care described by the Staff Observation Aggression Scale - Revised Emergency (SOAS-RE) - Grethe E. Johnsen; Tone Morken; Valborg Baste; Knut Rypdal; Tom Palmstierna; Ingrid Hjulstad Johansen (BMC, 2020)
Abstract Background Workplace violence in emergency primary health care is prevalent, but longitudinal studies using validated assessment scales to describe the characteristics of workplace violence in these settings are lacking. The aim of the present study was to determine the characteristics of aggressive incidents in emergency primary health care clinics in Norway. Methods Incidents of workplace violence were reported with the Staff Observation Aggression Scale - Revised Emergency (SOAS-RE). The study was conducted in ten emergency primary health care clinics over a period of one year. Results A total of 320 aggressive incidents were registered. The mean overall SOAS-RE score for reported aggressive incidents was 9.7 on a scale from 0 to 22, and 60% of the incidents were considered severe. Incidents of verbal aggression accounted for 31.6% of all reported incidents, threats accounted for 24.7%, and physical aggression accounted for 43.7%. Verbal aggression was most often provoked by long waiting time. Physical aggression was most often provoked when the patient had to go through an involuntary assessment of health condition. Almost one third of the aggressors were females, and nurses were the most frequent targets of all aggression types. No differences in psychological stress were found between types of aggression. Conclusions This study shows that workplace violence in emergency primary health care clinics is a severe problem. Patterns in provocation and consequences of aggressive incidents can be used to improve our understanding of and prevention and follow-up procedures of such incidents.